International travel and tourism - Andrews, Hugh (New York Alexis Press, LLC, 2023)
"This book tries to examine the complex global phenomenon of international tourism, exploring its various concepts in their different manifestations." --
Introduction -- Growth of travel and tourism through ages -- Growth and development of modern tourism -- The organization of travel and tourism -- Role of travel agency in tourism -- International travel services
Includes bibliographical references and index.
Keywords: Tourist trade; Tourism; Travel